2013
DOI: 10.1039/c3dt51197a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, spectral and redox switchable cubic NLO properties of chiral dinuclear iron cyanide/isocyanide-bridged complexes

Abstract: Two chiral dinuclear cyanide/isocyanide-bridged complexes (R)-[Cp(dppe)Fe-CN-Fe(dppp)Cp]PF6 (1[PF6]) and (R)-[Cp(dppe)Fe-NC-Fe(dppp)Cp]PF6 (2[PF6]), and their mono-oxidation products (R)-[Cp(dppe)Fe(II)-CN-Fe(III)(dppp)Cp] [PF6]2 (1[PF6]2) and (R)-[Cp(dppe)Fe(III)-NC-Fe(II)(dppp)Cp][PF6]2 (2[PF6]2) were synthesized and fully characterized. The electronic spectra of both the mixed-valence complexes 1[PF6]2 and 2[PF6]2 exhibit a strong and broad absorption band with two discernable peaks in the NIR region, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Therefore, the H 2 bpz ligand can provide a variable bridged conformation, and the size and topology of the resulting network can be adjusted. According to previous reports, we have found that the ligand has had important applications, such as electrocatalytic physical adsorption, metal–organic framework materials, rare-earth luminescence, and nonlinear optical materials. ,, Then we discovered that the H 2 bpz structure as an organic ligand can be combined with a metal salt through a simple hydrothermal reaction, which undoubtedly greatly reduced our workload in the actual process. , In the synthesis process, according to the more fluorine and less water hydrothermal method proposed by Weller et al, many people have reported the use of FP 6 – and SbF 6 – as the acid radicals of metal salts to synthesize coordination compounds and there were many types of noncentrosymmetric structures. In addition, the F – ion is beneficial for a blue shift of NCS compounds to overcome the red-shift phenomenon caused by cations such as SOJT . It can promote crystallization and can effectively improve crystal quality, which has a positive effect on crystal growth.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the H 2 bpz ligand can provide a variable bridged conformation, and the size and topology of the resulting network can be adjusted. According to previous reports, we have found that the ligand has had important applications, such as electrocatalytic physical adsorption, metal–organic framework materials, rare-earth luminescence, and nonlinear optical materials. ,, Then we discovered that the H 2 bpz structure as an organic ligand can be combined with a metal salt through a simple hydrothermal reaction, which undoubtedly greatly reduced our workload in the actual process. , In the synthesis process, according to the more fluorine and less water hydrothermal method proposed by Weller et al, many people have reported the use of FP 6 – and SbF 6 – as the acid radicals of metal salts to synthesize coordination compounds and there were many types of noncentrosymmetric structures. In addition, the F – ion is beneficial for a blue shift of NCS compounds to overcome the red-shift phenomenon caused by cations such as SOJT . It can promote crystallization and can effectively improve crystal quality, which has a positive effect on crystal growth.…”
Section: Resultsmentioning
confidence: 99%
“…Organic-based scaffolds have a broad band spectrum, nonlinearity, and fast response time features. They are also extensively adapted for the storage of optical data, processing of images, and optical switching applications. A comparative study between the organic and inorganic nonlinear chromophores reveals that organic systems have many preferable properties such as a short response time, large molecular plasticity, outstanding processing performance, and high nonlinear polarization rate. To achieve the required nonlinear optical characteristics, researchers have concentrated on synthesizing organic molecules with certain geometries and electronic molecular characteristics. …”
Section: Introductionmentioning
confidence: 99%